PWE-095 Fit Sample Stability for Haemoglobin-Positive Faeces Using Two Analytical Systems Over Seven Days. (17th August 2016) - Piggott, C; McDonald, P; John, C; Bruce, H
Abstract : Introduction: Automated quantitative faecal immunochemical test (FIT) for haemoglobin (Hb) systems include a faecal sampling device (with preservative buffer), laboratory analyser and reagent kit. In colorectal cancer screening programmes faecal samples are usually collected at home and posted back to the laboratory for testing. We investigated the likely effect of sample return time on Hb concentration using naturally Hb-positive faeces and two FIT systems. Methods: Eight Hb-positive faecal samples were taken from stools provided for calprotectin analysis and mixed for two minutes using wooden mixing sticks to distribute Hb. Up to 10 days elapsed before loading into sampling devices. FIT devices were loaded with faeces according to manufacturers' instructions for all eight samples in quadruplicate for the FOB Gold (Sentinel Diagnostics) and OC-Sensor Autosampling Bottle 3 (Eiken Chemical Co.). After mixing and incubation for 2–3 hours at room temperature, Hb was measured using the SentiFIT 270 and OC-Sensor PLEDIA analysers, respectively. Two of the sampling devices for each sample were stored at 19 o C (15–23 o C) and two at 6 o C (4–8 o C) for seven days. After mixing and allowing the 6 o C samples to warm to room temperature, Hb was re-measured on days 3, 5 and 7. Samples were also prepared using the Extel Hemo Auto MC Collection Picker/HM-JACKarc system (Kyowa Medex Co. Ltd.) but results are not included here due to pre-analytical sample preparation errors. Results: The percentage difference of the mean of the duplicate results from day 0 to days 3, 5 and 7 was calculated. Conclusion: Changes in Hb concentrations over seven days showed variation for both FIT systems, possibly due to differences in Hb degradation over time, or differences in individual portions of faeces that are loaded into the sampling devices and the time taken for Hb to move from the sampling stick to the buffer. The average, minimum and maximum percentage differences for the FOB Gold/SentiFIT 270 were lower than the OC-Sensor Autosampling Bottle 3/PLEDIA, possibly due detection of different Hb degradation products over time. Further work is needed to assess whether samples prepared sooner after collection would show the same differences. Disclosure of Interest: None Declared